KETAHANAN KELUARGA DAN PENCEGAHAN KEKAMBUHAN ADIKSI NARKOTIKA PADA REMAJA - Christiana, Christiana; Runturambi, Arthur Josias Simon; Mamoto, Benny Jozua (Social Welfare Study Program, 2023)
Abstract. Drug abuse among adolescents is a worrying public health problem in the world and in Indonesia. More than 2 million students have abused drugs and their first age was in their teens (Puslitdatin, 2019; Puslitdatin BNN, 2020). Drug abuse in adolescents affects individuals, families and communities and causes health, legal, social and economic losses (Chakravarthy et al., 2021; Sweatt, S.K, Gower, B.A, Chieh, A.Y, Liu, Y, Li, 2016). Adolescent drug abuse requires professional treatment in the form of rehabilitation, but the recurrence rate is high, even reaching 80% (Becker et al., 2021; Moos & Bernice, 2006; National Institute on Drug Abuse, 2020). Various studies mention the role of family and family resilience as important and influential in adolescent drug relapse rates (Becker et al., 2021; Ronel & Haimoff-Ayali, 2018; Zerbetto et al., 2017). Based on these data, this study intends to examine the role of the family in helping adolescents prevent relapse. The research in this paper uses research methods with the theoretical focus being Bandura's social learning theory and Shutherland's differential association theory. The theory holds up with family resilience in relapse. The novelty in this study specifically discusses the role of the family in adolescents by referring to Bandura and Shutterland's learning theory related to drug relapse and offers suggestions for solving it. Keyword: Addiction; drug abuse; family resilience. Abstrak. Penyalahguna narkoba di kalangan remaja merupakan masalah kesehatan masyarakat yang mengkhawatirkan di dunia dan Indonesia. Lebih dari 2 juta pelajar pernah menyalahgunakan narkoba dan usia pertama penyalahgunaan pada usia remaja (Puslitdatin, 2019; Puslitdatin BNN, 2020). Penyalahgunaan narkoba pada remaja berdampak bagi individu, keluarga dan masyarakat serta menimbulkan kerugian kesehatan, hukum, sosial dan ekonomi (Chakravarthy et al., 2021; Sweatt,S.K, Gower, B.A, Chieh, A.Y, Liu, Y, Li, 2016). Penyalahgunaan narkoba remaja memerlukan penanganan secara profesional berupa rehabilitasi, tetapi angka kekambuhan tinggi bahkan mencapai 80% (Becker et al., 2021; Moos & Bernice, 2006; National Institute on Drug Abuse, 2020). Berbagai studi menyebutkan peran keluarga dan ketahanan keluarga penting dan berpengaruh pada angka kekambuhan penyalahgunaan narkoba remaja (Becker et al., 2021; Ronel & Haimoff-Ayali, 2018; Zerbetto et al., 2017). Berdasarkan data tersebut maka penelitian ini bermaksud untuk mengkaji peran keluarga dalam membantu remaja mencegah kekambuhan. Penelitian dalam tulisan ini menggunakan metode tinjauan literatur dengan fokus teori yang digunakan adalah social learning theory Bandura dan differential association theory Shutherland. Teori tersebut dikaitkan dengan ketahanan keluarga dalam kekambuhan. Kebaharuan penelitian ini secara spesifik membahas peran keluarga pada remaja dengan mengacu pada teori pembelajaran Bandura dan Shutterland yang berkaitan dengan kekambuhan penyalahgunaan narkobanya serta menawarkan saran penyelesaiiannya. Kata kunci: Adiksi; ketahanan keluarga; penyalahgunaan narkoba.